WHO IS THE “MINER”? A BRIEF EXEGESIS OF JOB 28:4 - Paul M. Lipowski (European Scientific Journal, ESJ, 2015)
There is a long tradition of researching the book of Job and the meaning behind the imagery presented. Job 28:4, is not without its own imagery especially the image of the ―miner‖ and ―foreigner.‖ Unpacking the meaning behind the ―miner‖ and its use in the Old Testament, is quite interesting. Addressing the image of the ―miner‖ within the context of the book of Job and other books in the Old Testament shows the complex meaning of the search for wisdom. The analysis of the text provides evidence for the meaning of the image of the ―miner‖ as well as the overall search for wisdom. What is verse 4 telling its readers? How does it fit into the larger work of the book of Job? This work will address these questions and show that the 4th verse in the book of Job does indeed fit into wisdom literature.